ISOLASI LISOZIM ALBUMIN TELUR AYAM RAS DENGAN METODE KROMATOGRAFI PENUKAR ION - Zakiah Wulandari; Dedi Fardiaz; Maggy Thenawijaya; Nancy Dewi Yuliana; Cahyo Budiman (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2018)
Lysozyme is one of the proteins found in hen egg albumin. Besides known as antimicrobial agents, lysozyme hydrolysis products can also function as antioxidants and as angiotensin converting enzyme (ACE) inhibitors. The lysozyme is also known to have lysine and arginine that can give a sweet taste. The research aimed to isolate lysozyme from commercial laying hen eggs. The isolation and purification of the eggs lysozyme was done by preparative and analytical separation technique using cation exchange resins. The preparative separation was carried out by centrifugation of a large sample size of 205 g by centrifuga-tion, while the analytical separation only used only 3.16 g sample with a column measuring 13 cm in length and 3 cm in diameter. The number of samples isolated by preparative separation is greater than that with analytical method. The preparative separation was conducted in order to obtain the pure isolated lysozyme in higher quantity for further testing purposes. The purity of the isolated lysozyme from preparative separa-tion was 68.62% and the purity of isolated lysozyme from analytical separation was 63.03%.